Browsing Damage on Scots Pine: Direct and Indirect Effects of Landscape Characteristics, Moose and Deer Populations - Pfeffer, Sabine; Dressel, Sabrina; Wallgren, Märtha; Wallgren, Martha; Bergquist, Jonas; Kalén, Christer (2022)
Reducing browsing damages from cervids (Cervidae) on economically valuable tree species is a challenging task in many countries. Apart from cervid abundance, landscape characteristics, such as forest composition, land use, forage availability and climatic conditions, may affect the degree of browsing through both direct and indirect effects. A better understanding of basic mechanisms in this complex system is needed to design efficient and convincing management strategies. Focusing on Sweden as a case, which has been widely studied using regression analyses only, we applied path analysis to test the validity of a model on the indirect and direct links between landscape characteristics, cervid populations, and browsing damages on Scots pine (Pinus sylvestris). Our results validated the tested model in which moose (Alces alces) density and pine availability directly influence browsing damages. Increasing amounts of pine forests, preferred deciduous trees, and young forest had positive direct effects on moose densities and thereby indirectly contributed to increased browsing damages. The density of smaller deer species showed no direct effect on browsing damages on pine. Path analysis corroborated our attempt to disentangle direct and indirect potential causal drivers of browsing damages and shows that the choice of statistical method may alter the understanding of mechanistic driving forces.